Effect of 8 days of a hypergravity condition on the sprinting speed and lower-body power of elite rugby players - Barr, M. J.; Gabbett, T. J.; Newton, R. U.; Sheppard, J. M. (The Journal of Strength and Conditioning Research, 2015)
Sprinting speed and lower-body power are considered to be key physical abilities for rugby players. A method of improving the lower-body power of athletes is simulated hypergravity. This method involves wearing a weighted vest at all times during the day for an extended period of time. There are no studies that have examined the effect of hypergravity on speed or the benefit for rugby players. An experimental group (n = 8) and a control group (n = 7) of national team rugby players took part in the study, which consisted of rugby, conditioning, speed, and strength sessions. The experimental group wore a weighted vest equating to 12% of their body mass for 8 days. All players were tested for speed and lower-body power before, 2 days after, and 9 days after the intervention. Speed testing involved the athletes completing 40-m sprints with timing lights and high-speed video cameras assessing acceleration and maximal velocity sprinting kinematics. Lower-body power was assessed using weighted countermovement jumps (CMJs). No group differences were found for sprinting speed at any point. The experimental group displayed a large decrease in acceleration ground contact time (-0.01 ± 0.005 s, d = 1.07) and a moderate increase in 15-kg CMJ velocity (0.07 ± 0.11 m/s, d = 0.71). Individual responses showed that players in the experimental group had both negative and positive speed and power responses to the training intervention. Simulated hypergravity for 8 days is likely ineffective at improving sprinting speed while undergoing standard rugby training.